Strategi Integrated Marketing Communication Scomadi Indonesia dalam Meningkatkan Kesadaran Brand Awareness di Jakarta - Dhiasarafif Bucita Khalaflabib; Vilya Dwi Agustini; Titis Gandariani (JKOMDIS : Jurnal Ilmu Komunikasi Dan Media Sosial, 2026)
The growing trend of retro scooters in Jakarta presents significant market opportunities; however, Scomadi Indonesia, a brand that promotes the concept of “modern classic scooters”, faces the challenge of low brand awareness amid the dominance of competitors such as Vespa. This study aims to analyze the integrated marketing communication (IMC) strategies implemented by Scomadi Indonesia and to identify the supporting and inhibiting factors in building brand awareness. This study uses a qualitative approach with a case study method. Data analysis techniques follow the model developed by Miles, Huberman, and Saldana, which includes data collection, data condensation, data presentation, as well as drawing conclusions and verification. The results of the study indicate that Scomadi Indonesia implements all five components of IMC, namely advertising (online and offline), sales promotion, face-to-face sales, direct marketing, and public relations. The Scomadi Owners Indonesia (SOI) community contributes 60% to marketing effectiveness. Key supporting factors include top management support, a family-like culture, and a strong unique selling proposition. No inhibiting factors were identified; rather, they are viewed as challenges, namely the public’s perception of high prices and the long-established dominance of the Vespa brand. Scomadi’s brand awareness is at the brand recall stage